The active metabolite of Epimedii Folium promotes hippocampal neurogenesis in APP/PS1 mice by alleviating mitochondrial dysfunction - Bai, Jia-Ming; Li, Tong; Di, Xue; Yang, Jing-Xian; Cui, Zhao-Qi; Min, Dong-Yu; Shen, Yu-Feng; Shan, Si-Yu; Zhang, Ye-Xin; Shi, Yi-Jun; Xu, Zhi-Li; Dou, De-Qiang; et al. (Frontiers in Pharmacology, 2025)
IntroductionAlzheimer’s disease (AD), the most common form of dementia, currently has no effective cure. Epimedii Folium (EF), a traditional Chinese medicine known as Yin-yang-huo, has demonstrated significant neuroprotective properties.Methods In this study, neural stem cells overexpressing the APPswe gene (APP-NSCs) were used as an in vitro AD model. The CCK-8, LDH, neurosphere formation, and BrdU incorporation assays were employed to identify the most effective bioactive metabolite of EF in promoting NSC proliferation. Subsequently, JC-1 staining, ATP quantification, and ROS assays were conducted to evaluate the protective effects of Icariside II (ICS II)-identified as the most effective metabolite-on mitochondrial function. APP/PS1 transgenic mice received an oral administration of 10 mg/kg ICS II for 7 weeks. Cognitive function was assessed using the Morris water maze and nest-building tests, while H&E and Nissl staining were used to evaluate brain tissue pathology. Transmission electron microscopy (TEM) examined the ultrastructural integrity of hippocampal neurons, immunofluorescence assessed hippocampal neurogenesis, and Western blotting quantified proteins involved in mitochondrial dynamics. Additionally, Rotenone (Rot), a mitochondrial respiratory chain inhibitor, was applied to disrupt mitochondrial function, allowing an evaluation of whether the neurogenesis-promoting effect of ICS II depends on maintaining mitochondrial structure and function.Results and discussion The results demonstrated that ICS II exhibited the strongest capacity to promote APP-NSC proliferation (P < 0.01, η2 = 0.845), followed by Icariin and Icaritin. ICS II treatment significantly ameliorated cognitive deficits (P < 0.01, η2 = 0.883), neuronal damage, and impairments in neurogenesis in adult APP/PS1 mice. Moreover, ICS II rescued mitochondrial damage by upregulating fusion proteins (Mfn1 and Mfn2) and downregulating fission proteins (p-Drp1/Drp1 and Mff); however, these protective effects were negated by Rot administration. In conclusion, this study identifies ICS II as one of the most effective metabolites of EF, promoting hippocampal neurogenesis and alleviating mitochondrial dysfunction in APP/PS1 mice, thereby offering promising therapeutic potential for AD.